Eliminating supportive crowds reduces referee bias. (24th December 2021) - Reade, J. James; Schreyer, Dominik; Singleton, Carl
Abstract: We use a series of historical natural experiments in association football to test whether social pressure from a home stadium crowd affected behavior and outcomes. The standout effect of an empty stadium was that referees cautioned visiting players less often, by over a third of a yellow card per match or once for every 22 fouls committed. Stadium crowds caused referees to favor the home team in their decision‐making. Empty stadiums appear to have reduced the overall home advantage in the final outcomes of football matches, but we cannot statistically reject no effect.